Gallbladder and other pathologies: 7,788 cases, a cohort study in North Western India - Bhushan Sanjay Bhalgat; Pinakin Patel; Suresh Singh; Phanindra Swain; Pravin Kumar; Kamal Kishor Lakhera; Bhairu Gurjar; Raj Govind Sharma; Ashwini Dilip Haibatpure (Brazilian Journal of Oncology, 2022)
Introduction: Gallbladder diseases are a well-studied subset of diseases in the Gangetic belt of India. But, the prevalence of gallbladder diseases, both benign and malignant (as a whole subset) has not been studied in Eastern Rajasthan yet. This study aims to provide an epidemiological overview of all histopathologically proven gall bladder diseases from standard pathology laboratories of Jaipur. Material and Methods: In this chart review analysis, we scrutinized all the records of histopathologically proven diseases at four major pathology departments and labs in Jaipur, Rajasthan over five years; of which 7,788 patients had gallbladder pathologies. We harnessed this raw data of gall bladder pathologies to obtain meaningful results. Results: Histopathological analysis revealed the percentage of gall bladder diseases overall of all the histopathologically proven diseases, in Rajasthan as 2.59%. The malignant pathologies accounted for 2.65% of it. Cholelithiasis (41.32%) was the most common benign pathology with acute cholecystitis with cholelithiasis (29.49%), chronic cholecystitis with cholelithiasis (18.73%), acute cholecystitis (8.28%), acalculous cholecystitis (1.11%), reactive hyperplasia (0.69%), mucocele (0.09%) and xanthogranulomatous cholecystitis (0.08%) in descending order of frequency. Adenocarcinoma (83.49%) was the most common malignant pathology found, followed by undifferentiated carcinoma (5.34%), squamous cell carcinoma (4.85%) and adenosquamous carcinoma (1.94%) in that order. Gradewise, malignancies were the most commonly of grade 2. The sex ratio favoured females in both the subsets; being 1:4 for benign and 1:2 for malignant pathologies. 61 to 70 years of age is the most affected age group for gall bladder malignancies for both the sexes. Conclusion: This study would make the difference in the national average and contribute hugely to the national registry, since it showcases the analysed data from a large geographic location of the country. It would also benefit the clinicians of Rajasthan in better decision-making for the patients of this region.